AWA - Sistema de monitoramento residencial de GLP com alerta - Santana, Alexandre Pedro (2021)
The Internet of Things (IoT) allows the communication of machines with machines, like a new internet model. From this, this work presents a solution that employs IoT in the development of a platform to assist in the control and monitoring of gas consumption (LPG), in addition to issuing an alert in case of leak detection through an application. This project features a hardware and a software platform, called AWA, composed of ESP32 microcontroller, responsible for communication, sensors (load cell and MQ6, for monitoring the weight of the cylinder and detecting leaks), and the actuator HX711, which amplifies the signal from the sensors, transmitting to the microcontroller. This information collected from AWA is sent by the microcontroller to a mobile application which makes the data available to the user. Thus, the daily consumption of LPG and the alert of possible leaks can enable the consumer to control their expenses with gas and, most importantly, to possibly avoid accidents involving gas cylinders.